SOCIAL PRACTICE OF SEXUAL VIOLENCE IN SOCIETY (CASE STUDY IN PADANG CITY) - Maihasni, Maihasni; Fachrina, Fachrina; Anggraini, Nini (LPPM Universitas PGRI Sumatera Barat, 2022)
There is not a day without sexual violence to children in mass media. Some people think that Indonesia has emergency case of sexual violence. Padang city is belong to this phenomena, such as 5 students of elementary school were victims of sexual harassment by a sports teacher, sexual harassment in public transportation, sodomy of 3 students, rape of a disabled woman by her brother-in-law, and rape by her stepfather, parking attendant and employer. The worst case is a sexual harassment by legislative candidate in 2018 and 2 bilogical children by their father in 2020. Government and non-Governmental institutions have been doing many efforts to prevent and cope of sexual violence. However, cases still happen. For this reason, the study tried to analyze why sexual violence still occurs even though various efforts have been made. The study used a qualitative approach with a descriptive type. The selection of informants used purposive sampling. Data collection used depth interviews and literature review. The results found that sexual violence occurs in girls under the age of 12 years. The actors are dominated by the closest people such as father, siblings, uncles, teachers, neighbors and a official. The encourage factors of sexual violence in the community are related to the mentality of the perpetrator, powerlessness of the victim, lack of communication and social control of parents, lack of religious knowledge, pornography and poverty. Meanwhile, the disencourage factors of sexual violence itself, such as; sex education, doing positive activities, social control and sanctions and severe punishment for perpetrator.